Present Day Development and Future Perspectives of Turkish-Kyrgyz Relations - AALAI, GÜLŞANA (İstanbul Kültür Üniversitesi, 2023)
In the light of Central Asia's geopolitical situation, this paper examines Kyrgyz- Turkish political and military cooperation. Its goal is to learn more about the challenges and opportunities that the two countries' bilateral relations present. The chronological framework of the study covers the period from 1991 to 2021. The time frame of this work allows one to fully trace the dynamics of changes in political and military processes in Central Asia, to explore the evolution of the foreign policy strategies of Turkey in Kyrgyzstan. The study has revealed that Kyrgyzstan continues to be a zone of competition in the implementation of the regional foreign policy aspirations of Russia and Turkey. Therefore, the process of interaction requires the development of a flexible and variable policy. The regional powers have different interests in Kyrgyzstan, so their activities in this country are not only in the nature of cooperation in security issues, but also rivalry in cultural and educational policies. The Turkish authorities are trying to optimize the policy aimed at developing further integration with the Central Asian republics, including Kyrgyzstan, both on a multilateral platform and on a bilateral basis.
Türk-Kırgız İlı̇şkı̇lerı̇nı̇n Günümüzdekı̇ Gelı̇şı̇mı̇ ve Gelecek Perspektı̇flerı̇
▪ Yüksek lisans tezi.
Keywords: Central Asia Geopolitics; Turkish Foreign Policy; Kyrgyzstan; Hard and Soft Power